Adverse Pregnancy Outcomes in Nondiabetic Patients with an Elevated Early Pregnancy HbA1c - Bender, Whitney R.; McCarthy, Clare; Elovitz, Michal; Parry, Samuel; Durnwald, Celeste (American Journal of Perinatology, 2022)
Objective This study aimed to evaluate the impact of elevated early hemoglobin A1c (HbA1c) values on perinatal outcomes in patients without a diagnosis of diabetes or gestational diabetes.Study Design This is a retrospective study of patients with a singleton pregnancy who underwent universal HbA1c screening in early pregnancy at an urban tertiary care center between December 1, 2016, and December 31, 2018. Patients with pregestational diabetes mellitus (DM) and gestational DM (GDM) were excluded from analysis. The exposure of interest was HbA1c of 5.7 to 6.4% as measured on routine prenatal bloodwork at or during 16 weeks' gestation. The following pregnancy outcomes were assessed: preterm delivery <37 weeks, hypertensive disorders of pregnancy, shoulder dystocia, macrosomia (birth weight >4,000 g), small or large for gestational age neonate, operative vaginal delivery, third- or fourth-degree lacerations, cesarean delivery, neonatal intensive care unit (NICU) admission, neonatal hypoglycemia, and neonatal hyperbilirubinemia. Multivariable regression was performed to assess the relationship between HbA1c and selected adverse outcomes while controlling for potential confoundersResults Of the 2,621 patients who met inclusion criteria, 334 (12.7%) had an elevated HbA1c of 5.7 to 6.4%. Patients with an elevated HbA1c were more likely to be older, Black, multiparous, publically insured, obese, or have chronic hypertension than patients with normal HbA1c values. In the unadjusted analysis, patients with an elevated HbA1c were less likely to deliver at term (84.7 vs. 92.4%, p = 0.006), but more likely to undergo cesarean section (32.8 vs. 27.6%, p = 0.038), develop hypertensive disorders of pregnancy (31.9 vs. 23.2%, p = 0.001), or deliver a macrosomic infant (10.5 vs. 6.8%, p = 0.016) than those with a normal A1c. After adjusting for race, body mass index, insurance status, nulliparity, and age, however, only the relationship between HbA1c and spontaneous preterm birth remained significant (adjusted odds ratio [aOR] = 1.76, 95% confidence interval [CI]: 1.01–3.07).Conclusion In our urban population, an elevated early HbA1c was associated with spontaneous preterm birth in nondiabetic patientsKey Points
Keywords: HbA1c; preterm birth; adverse outcomes; glucose tolerance